Database systems for advanced applications : DASFAA 2016, International Workshops: BDMS, BDQM, MoI, and SeCoP, Dallas, TX, USA, April 16-19, 2016. Proceedings /: DASFAA 2016, International Workshops: BDMS, BDQM, MoI, and SeCoP, Dallas, TX, USA, April 16-19, 2016. Proceedings. (2016) - Unknown
No abstract available